PEMANFAATAN LAHAN SECARA KONSERVATIF BAGIAN HULU SUNGAI CIWALEN DARI DAS CITANDUY UNTUK MENDUKUNG KETAHANAN PANGAN MASYARAKAT - SITI FADJARAJANI; ERWIN HILMAN HAKIM; ELY SETIYASIH ROSALI; DARWIS DARMAWAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The river has ver important function for the life of living things, the need for river management with the aim of preservation, harmony of the ecosystem and increasing the balanced utilization of natural resources for humans. Ciwalen river is included in one of the upstream rivers of the Citanduy River Basin starting from Gunung Cakrabuana, has an administrative location in Nanggewer Village, Pagerageung district or is in the north of Tasikmalaya Regency. Citandung watershed in one of the critical watersheds of 108 critical watersheds in Indonesia, based on the medium term development (RPJM) for 2010 – 2014, the Citanduy watershed is one of the watersheds proposed as priority watersheds in the 2020 – 2024 KLHK srategic plan. The upstream part of the Ciwalen River from the Citanduy River Basin, based on the geological Map of the Tasikmalaya Sheet, West Java, is located on Gunung Cakrabuana which is an old volkanic product with latoson – Andosol soil types which have a rather sensitive level of erosion, erosion faktors can also be caused by community acivities. The formation of the Segara Anakan Lagoon can be used as evidence that the level of erosion is strong in the Citanduy River Basin. Efforts to minimize the increase in the rate of erosion by carrying out convervation through vegetative methods and involving community participation by implementing the heritage of the Sundanese community related to environmental values, this is done to increase water infiltration of optimize the potensial of natural resources. As an effort to address the problems that accur in the Citanduy watershed through community service, namely conducting socialization on river convervation, providing an understanding of the contribution of rivers in realizing food security, and instilling an understanding of the existence of rivers that must remain sustainable. Community service activities in Nanggewer Village show that the level of community pariticipation in this activity is very high starting from the socialization to the conservation form of land use, namely planting trees and plants, wih the awareness tha there is a balance berween meeting the needs of the natural environment and the community’s needs for good food security in the long term. In short and increasing the community’s economy in the long run through natural tourism.